Herbal Mouthwash Containing Extracts of Baccharis dracunculifolia as Agent for the Control of Biofilm: Clinical Evaluation in Humans - Vinícius Pedrazzi; Mateus Freire Leite; Reisla Cristina Tavares; Sandra Sato; Glauce Crivelaro do Nascimento; João Paulo Mardegan Issa (The Scientific World Journal)
Baccharis dracunculifolia DC (Asteraceae), popularly known as “alecrim-do-campo,” is largely distributed in South America, is shown to exhibit protective actions against gastric ulcers, has anti-inflammatory properties, and is hepatoprotective. Several essential oils obtained from Baccharis species possess biological activities, such as antimicrobial and antivirus activities. This randomized controlled trial evaluated the efficacy of B. dracunculifolia in the reduction of dental biofilm, comparing this natural product with other mouthwashes already known in the dental market. In measuring the time after use of mouthwash (t=1), there was no difference between products (P=0.602); that is, subjects in the study had a similar PI after the first use. After one week (t=2), there was no difference between the four products evaluated (P=0.674), so, all research individuals completed the study with a similar reduction in dental biofilm between themselves but it was different from initial state (Friedman test). It is possible to conclude that B. dracunculifolia had the same efficiency of the materials used to oral hygiene in reduction of dental plaque and, consequently, prevention of dental caries. Thus, we can consider B. dracunculifolia as a good candidate for new material to be implemented in dental care.